PEACEFUL APPLICATIONS OF NUCLEAR TECHNOLOGY AND ITS CHALLENGES - Akinola, Akinjide A; Ojinnaka, Chukwudi A. S.; Kuye, Ayoade (Journal of Engineering and Technology (JET), 2026)
Nuclear Technology is perceived as destructive because its first widely publicized use was in Hiroshima and Nagasaki, Japan, where nuclear bombs destroyed the two cities and many lives, subsequently ending the Second World War. However, there are numerous peaceful uses of nuclear technology, including electricity generation, medicine, food and agriculture, the process and petroleum industry, commerce and space. The article describes nuclear energy’s origin, explains some introductory nuclear physics concepts, and represents many nuclear technology applications. Finally, the pros and cons of using nuclear technology for each application and its future uses are discussed.